Theory of Dynamic Atomism in Lithuanian Schools in the Second Half of the 18th Century - Plečkaitis, Romanas (Problemos, 1968)
R. J. Boscowich’s follower in Lithuania Dionysius – his real name is not yet ascertained – professor of philosophy at the Vilnius Trinitarian College in 1763 to 1765, delivered the theory of dynamic atomism in his lecture course of physics. Dionysius made important physical and philosophical conclusions. He treated matter, movement, space and time as a unity, emphasizing their relativity. In cosmology he supported the idea of plurality of universes and advocated N. Copernicus’ system. Dionysius presented a new physical-philosophical understanding of the universe which in some aspects approaches the contemporary understanding.